2000
DOI: 10.1302/0301-620x.82b1.0820017
|View full text |Cite
|
Sign up to set email alerts
|

Test of stability as an aid to decide the need for osteotomy in association with open reduction in developmental dysplasia of the hip

Abstract: After open reduction for developmental dysplasia of the hip (DDH), a pelvic or femoral osteotomy may be required to maintain a stable concentric reduction. We report the clinical and radiological outcome in 82 children (95 hips) with DDH treated by open reduction through an anterior approach in which a test of stability was used to assess the need for a concomitant osteotomy. The mean age at the time of surgery was 28 months (9 to 79) and at the latest follow-up, 17 years (12 to 25). All patients have been fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
5
31
0
2
Order By: Relevance
“…Forlin et al [26] reported that there were no significant differences in outcome with regard to age at the initial reduction, treating 72 hips by CR. In contrast, Zadeh et al [27] treated 95 cases of DDH by OR combined with osteotomy and concluded that age 2 years at surgery is associated with a favourable outcome. Cıtlak et al [28] reported that acetabular development was better in patients treated before the age of 18 months, based on their evaluation of 110 hips treated by medial OR, while additional operations were performed on 32 hips (29%).…”
Section: Discussionmentioning
confidence: 96%
“…Forlin et al [26] reported that there were no significant differences in outcome with regard to age at the initial reduction, treating 72 hips by CR. In contrast, Zadeh et al [27] treated 95 cases of DDH by OR combined with osteotomy and concluded that age 2 years at surgery is associated with a favourable outcome. Cıtlak et al [28] reported that acetabular development was better in patients treated before the age of 18 months, based on their evaluation of 110 hips treated by medial OR, while additional operations were performed on 32 hips (29%).…”
Section: Discussionmentioning
confidence: 96%
“…It was not possible to ascertain AVN rates, clinical and radiological results, and need for further operative intervention for all 18 articles, and where available, heterogeneity was noted in the reporting of results. Data were often pooled in mixed groups, which was adequate to quote the overall outcome rates for all surgery involving an anterior open reduction [5,26,30,32,45]. However, for subgroup analysis by specific surgical prescription, additional data were excluded, and fewer studies still had individual patient data for further analysis [3,28,30,31,39,40,46].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous advocates of a single-stage surgical approach to this problem combining open reduction and pelvic and femoral osteotomy, to minimize need for future intervention [11,12,39]. Others deem this too aggressive an approach and base management on intraoperative stability and subjective assessment of soft tissue tension [22,45]. Ultimately the surgical aim is to undertake the minimum amount of intervention necessary to obtain a stable concentric reduction, avoiding AVN or further surgical procedures to provide a pain-free hip that will last decades.…”
Section: Introductionmentioning
confidence: 99%
“…This simultaneous approach renders immediate stability to the surgically reduced hip and minimises the need for secondary procedures to correct residual acetabular dysplasia [14,15]. Surgical relocation of the hip in isolation renders adequate stability in only 2-37% of cases over 12 months of age [9,10]. The complication rate with combined treatment modalities compares favourably to that of staged surgical procedures [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Stability of the reduced hip is assessed intra-operatively. Should instability be present with the hip in extension, the acetabular deficiency is located mainly anterior, and if instability is present in adduction, the deficiency is more lateral [9,10]. This information helps to determine the amount and direction of the acetabulum roof displacement (acetabuloplasty) to render the required coverage of the femur head.…”
Section: Surgical Techniquementioning
confidence: 99%